Meningkatkan Hasil Belajar dengan Perhatian Orang Tua - Deisye Supit (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
Parental attention is needed in improving student learning outcomes, for this reason this study aims to find out whether parental attention can improve student learning outcomes. This research uses descriptive quantitative with convenience sampling. There are two variables in this study, the independent variable is parental attention, and the dependent variable is student learning outcomes. This research was carried out in one of the Manado Junior High Schools. Respondents amounted to 64 students. The results obtained in this study are as follows: The level of parental attention is at a good level, the level of student learning outcomes is at a good level and the relationship between parental attention and student learning outcomes is P = .092. The result is that there is no significant relationship between parental attention and student learning outcomes. Suggestions to parents of students that the attention given by parents should be increased. For parents to increase the attention that must be given to children and realize that student success cannot be separated from their attention. For students, it is expected that learning outcomes will be improved in order to get better results.